Effect of Nasa Liquid Organic Fertilizer and NPK Mutiara Fertilizer on the Growth and Yield of Tomato (Lycopersicum esculentum Mill.) Servo F1 Variety - Ardani Ardani; Akas Pinaringan Sujalu (Universitas 17 Agustus 1945 Samarinda, 2019)
Effect of Nasa Liquid Organic Fertilizer and NPK Mutiara Fertilizer on the Growth and Yield of Tomato (Lycopersicum esculentum Mill.) Servo F1 Variety. The purpose of the research is to study the effect of Nasa liquid organic fertilizer and NPK Mutiara fertilizer and its interaction on the growth and yield of tomato, as well as to find the proper concentration of Nasa liquid organic fertilizer and dosage of NPK Mutiara fertilizer for obtaining the best yield of tomato.The research was conducted for three months from February to April 2017, from the time of seed preparation, land preparation until harvest time. It was carried out in Pinang Village, Samarinda Ulu Regency, East Kalimantan Province.The research was conducted using Completely Randomized Design (CRD) in 4 x 4 Factorial Experiment and three replications. The first factor was the concentration of Nasa liquid organic fertilizer (P) consisting of 4 levels : no Nasa liquid organic fertilizer application (p0), 1 ml/l water (p1), 2 ml/l water (p2), and 3 ml/l air (p3). The second factor was the dosage of NPK Mutiara fertilizer (N) consisting 4 levels : no NPK Mutiara fertilizer application (n0), 5 g/polybag (n1), 10 g/polybag (n2), and 15 g/polybag (n3).The results showed that Nasa liquid organic fertilizer, NPK Mutiara fertilizer treatment its interaction affected very significantly on the plant height at age 15, 30 and 45 days after planting, age of plants flowered, age of plant harvested, number of fruits per plant, and weight of fruits per plant; and the weighest weight of fruits per plant was produced in 2 ml/l water POC Nasa and 10 g/polybag of NPK Mutiara fertilizer (p2n2) treatment of 840,00 g/plant, while the lighest one was produced in 1 ml/l water POC Nasa and no NPK Mutiara fertilizer (p1n0) treatment of 300,00 g/plant